Inspection on a Three-Dimensional Measuring Machine for a Virtual Model for Additive Manufacturing - Ameddah, Hacene; Selloum, Rabia; Brioua, Mourad (International Conference on Advances in Mechanical Engineering and Mechanics, 2020)
Today, and to quickly meet the high demands of variability, supply chain efficiency and energy optimization, business markets are looking for modern manufacturing technologies and as a solution, industry 4.0 is using the benefits of integrating modern manufacturing technologies and information systems to promote production capabilities. In this context, intelligent industry represents a new generation of automatic production systems based on the concepts of intelligent industry, intelligent manufacturing, control and intelligent inspection, such as inspection on coordinate measuring machines (CMMs). This technology allows many machines to be integrated into a plant and controlled online using the MBD (Model Based Design) quality system. The problem of conformity of parts with complex geometry is becoming more and more important. The objective of this work is to present a 3D inspection technique on a virtual model (MBD: Model Based Design), using a coordinate measuring machine equipped with a “POWER INSPECT” measurement and inspection software. The interest of this technique is to show the impact of the dimensional inspection and geometric tolerance process of the CAD model for the CAI (Computer aided Inspection) approach on the fidelity of the finished product for additive manufacturing (AM) including intelligent industry.